Instructor teaching a group of girls how to swim at a swimming hole - Unknown:::Creator::::::::::::
Photograph shows a group of girls lined up in the water of a swimming hole watching a woman teach the proper stroke for freestyle swimming. The instructor is standing on the shore. Some of the girls are practicing the stroke and one girl is away from the group much further out into the swimming hole. They are probably from the YWCA's Camp Ayun Mapu in Big Basin.